Accounting for diverse risk attitudes in measures of risk perceptions: A case study of climate change risk for small-scale citrus farmers in Indonesia. (June 2020) - Hasibuan, Abdul Muis; Gregg, Daniel; Stringer, Randy
Highlights: Farmer households have complex risk attitudes. RPI is inadequate to explain endogenous variable relationship with risk perception. RPI can be used prioritise climate-related intervention program or policies. Information technology-based extension methods have a higher opportunity for farmers. Abstract: Climate change is likely to generate severe impacts on smallholder farmers in developing countries. As key drivers of adaptation, climate risk perceptions are highly heterogeneous, varying both across people and context, and are complex, being defined as behaviour which varies across both impact and likelihood dimensions in non-linear ways. Yet most studies examining risk perceptions are unable to disentangle the role of perceptions regarding impacts from those regarding the likelihood of climate-related events taking place. This paper presents a decomposition and associated analysis of survey-based 'risk perception' measures. The decomposition we apply allows independent accounting for perceptions over frequencies and impacts linking to behavioural patterns of risk attitude. The approach presented here draws on a detailed 2017 survey of 500 farmers in rural Indonesia to generate insights into the relationship between risk perceptions and extension services, accessibility of information, and other factors. Results show that risk perceptions are generated from complex interaction between perceived future frequencies and outcomes of climate events and indicate differential impacts of extension services across these perceptions. This paper also presents empirical support for the use of information and communication technology based extension as an efficient extension tool to reach more farmers than in traditional methods.